Activity of apremilast in a patient with severe pemphigus vulgaris: case report - Delvaux, Cheyenne; Bohelay, Gérôme; Sitbon, Ishaï-Yaacov; Soued, Isaac; Alexandre, Marina; Cucherousset, Joël; Gilardin, Laurent; Diep, Antoine; Caux, Frédéric; Le Roux-Villet, Christelle (Frontiers in Immunology, 2024)
Introduction Although the treatment for pemphigus vulgaris (PV) has been revolutionized by the use of rituximab combined with corticosteroids, new effective therapies with a better safety profile are needed. Observation A 67-year-old woman was diagnosed with severe mucosal PV, which was initially misdiagnosed as atypical Behçet's disease. Following an unsuccessful colchicine treatment, significant improvement was observed upon the introduction of apremilast: reduced pain, fewer lesions, and a stabilized weight. The discontinuation of apremilast led to a rapid relapse. Retrospective analysis through anti-Dsg3 ELISA indicated a gradual decrease in antibody levels during the apremilast treatment. Discussion Apremilast, a phosphodiesterase 4 inhibitor approved for psoriasis and Behçet's disease's related oral ulcers treatment, demonstrated its efficacy in this PV case. This is the second case report highlighting the effectiveness of apremilast for PV treatment. Apremilast's ability to upregulate cyclic adenosine monophosphate (cAMP) levels appears to contribute to the stabilization of keratinocyte adhesion. Conclusion Apremilast may be a promising therapeutic option for the treatment of pemphigus, with an innovative mechanism of action, no induced immunosuppression, and good tolerance. It could be a good alternative to steroids, in the treatment regimen of steroids combined with rituximab.